Influence of the Distance between Focusing Lens and Target Surface on the Characteristics of Laser-excited Lead Plasma - Abbas, Qusay Adnan (Iraqi Journal of Science, 2021)
The present work investigated the effect of distance from target surface on the parameters of lead plasma excited by 1064nm Q-switched Nd:YAG laser. The excitation was conducted in air, at atmospheric pressure, with pulse length of 5 ns, and at different pulse laser energies. Electron temperature was calculated by Boltzmann plot method based on the PbI emission spectral lines (369.03 nm, 416.98 nm, 523.48, and 561.94 nm). The PbI lines were recorded at different distances from the target surface at laser pulse energies of 260 and 280 mJ. The emission intensity of plasma increased with increasing the lens-to-target distance. The results also detected an increase in electron temperature with increasing the distance between the focal lens and the surface of the target in all laser energies under study. In addition, the electron number density was determined by using the Stark broadening method. The data illustrated that the electron number density was increased with increasing the distance from target surface, reaching the maximum at a distance of 11 cm for all pulse laser energy levels under study.